Managing the MNE subsidiary: Advancing a multi-level and dynamic research agenda - Meyer, Klaus E.; Li, Chengguang; Schotter, Andreas P. J. (Journal of international business studies, 2020)
Multinational enterprise (MNE) subsidiaries abroad are important organizations in their own rights. They typically hold some of the MNE’s most critical resources, and operate at the forefront of complex international environments. In this review, we identify and organize theoretical and empirical research on subsidiary management based on over 600 articles in leading academic journals. We develop a conceptual framework that integrates complementary streams of theoretical and empirical research with the subsidiary as its focal unit of analysis. In particular, we review six lines of research on subsidiary scope, practices, knowledge management, engagement with local market and nonmarket actors, performance, and individuals within subsidiaries. We highlight theoretical perspectives that have contributed to, and been advanced by, research on MNE subsidiaries. Based on the review, we explore future research agendas, linking the contemporary research themes with two main thrusts. First, subsidiary management is a multi-level phenomenon that would benefit from more microfoundational research. Second, subsidiary management operates at key interfaces of technology paradigm shifts, and of disruptions in the political and institutional environment. Research into the dynamics of subsidiary management would thus enhance our understanding of international business in a volatile global economy.